2020
DOI: 10.1007/s12397-020-09320-8
|View full text |Cite
|
Sign up to set email alerts
|

Antisemitism on a California Campus: Perceptions and Views Among Students

Abstract: This article explores the relationship between antisemitism and anti-Israel attitudes among university students. Critics maintain that hostility toward Israel is an indicator of the "new antisemitism." Activists and their advocates insist that anti-Israel attitudes and behaviors reflect a political conflict and have little to do with antisemitism. Existing empirical scholarship shows a strong link. Evidence is presented from a survey of a random sample (N = 468) of undergraduate students at the University of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 18 publications
2
8
1
Order By: Relevance
“…Respondents who held strongly anti-Israel views (e.g., believing that Palestinian suicide bombers against Israeli civilians are justified) were also likely to hold antisemitic beliefs that are completely unrelated to the Israel/Palestine conflict (e.g., believing Jews have too much power in finance). Other studies have found a similar relationship (Beattie 2017; Smith and Schapiro 2019; Cohen et al 2009; Shenhav-Goldberg and Kopstein 2020).…”
Section: Antisemitism On the Left And Rightsupporting
confidence: 70%
See 1 more Smart Citation
“…Respondents who held strongly anti-Israel views (e.g., believing that Palestinian suicide bombers against Israeli civilians are justified) were also likely to hold antisemitic beliefs that are completely unrelated to the Israel/Palestine conflict (e.g., believing Jews have too much power in finance). Other studies have found a similar relationship (Beattie 2017; Smith and Schapiro 2019; Cohen et al 2009; Shenhav-Goldberg and Kopstein 2020).…”
Section: Antisemitism On the Left And Rightsupporting
confidence: 70%
“…Young people—college students in particular—typically exhibit more tolerant and cosmopolitan attitudes than older people. This might suggest lower levels of antisemitism (Shenhav-Goldberg and Kopstein 2020; Federico and Sidanius 2002). However, unlike other prejudicial attitudes that have been found to be more common in older adults than younger adults, such as sexism and racism (Stewart, von Hippel and Radvansky 2009; Janmaat and Keating 2017), several prior studies have shown that antisemitism is actually more common among young people.…”
Section: Antisemitism On the Left And Rightmentioning
confidence: 99%
“…Despite younger generations generally exhibiting more cosmopolitan and less prejudicial attitudes (Federico and Sidanius 2002;Shenhav-Goldberg and Kopstein 2020), we find that young Black and Hispanic adults express equal or higher levels of antisemitic attitudes than older Black and Hispanic adults; only young White adults express lower levels of antisemitism than their older counterparts. Young Black and Latino respondents answer this battery of antisemitism questions similarly to how young White alt-right respondents do.…”
Section: Discussioncontrasting
confidence: 58%
“…One such theory is that racial minority groups in the United States identify with Palestinians, who they view as non-White, and against Israelis, who they view as White. In this theory, minority groups hold negative views toward American Jews because American Jews largely support a country that, in the eyes of Israel's opponents, is a (White) oppressor regime (Forman 1998;King and Weiner 2007;Lipstadt 2019;Rubin 1997;Shenhav-Goldberg and Kopstein 2020).…”
Section: The Roots Of Minority-group Antisemitismmentioning
confidence: 99%
“…The results in Tables 2a and 2b show that three items correlate more heavily with anti‐semitism scores than others. In particular, the three items tapping strongly into important dimensions of anti‐semitism (items 1, 2, and 5), which correlate strongly with each other in previous studies (Shenhav‐Goldberg and Kopstein 2020), correlate strongly with anti‐semitism scores. The stronger correlation may be, to some extent, a result of the wording of the survey instrument, as items 1, 2, and 5 were asked using negative prompts, while items 3 and 4 were asked using positive ones.…”
Section: Datasupporting
confidence: 51%